2011
DOI: 10.1007/s10329-011-0281-3
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of infection by Platynosomum illiciens (Braun, 1901) in captive neotropical primates

Abstract: Platynosomum illiciens (Trematoda, Plagiorchida) is a trematode parasite reported in felids and falconiforms. It was identified in the gall bladder of eight captive neotropical necropsied primates from the National Primate Center (CENP), Ananindeua, State of Pará, Brazil. This is the first description of Platynosomum illiciens as a parasite of primates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…In a recent study, the authors concluded that P. amazonensis and P. marmoseti should be synonymized with P. illiciens [28]. In one study, eggs of P. illiciens measured, on average, 40.1 mm long and 26.6 mm wide [29]. Terrestrial snails serve as first intermediate hosts, whereas terrestrial isopods serve as second intermediate hosts.…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, the authors concluded that P. amazonensis and P. marmoseti should be synonymized with P. illiciens [28]. In one study, eggs of P. illiciens measured, on average, 40.1 mm long and 26.6 mm wide [29]. Terrestrial snails serve as first intermediate hosts, whereas terrestrial isopods serve as second intermediate hosts.…”
Section: Etiologymentioning
confidence: 99%
“…Prevalence of infection of wild marmosets can be high. In captive situations where the intermediate and paratenic hosts are available, thereby facilitating completion of the life cycle, infection rates may remain high [29,33]. Cats also serve as definitive hosts and thus may constitute an important reservoir of infection in some environments [30].…”
Section: Epizootiologymentioning
confidence: 99%
“…in the liver of a congeneric primate species, C. jacchus, were shown to be portal fibrosis, ascending cholangitis, cholestasis, and even secondary biliary cirrhosis (Sousa et al 2008). Infections with this trematode genus currently pose a problem for other primate centers throughout Brazil (Sousa et al 2008;Silva et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…), Old World (Macaca fascicularis) and New World monkeys (Callicebus moloch, Callimico goeldii, Callithrix spp., Cebuella pygmaea, Chiropotes satanas, and Saguinus spp.) (KINGSTON & COSGROVE, 1967;COSGROVE et al, 1968;SHANTA, 1970;PORTER, 1972;TANTALEAN et al, 1990;WARREN et al, 1998;MELO, 2004;KAWHAGE et al, 2005;SOUSA et al, 2008;SILVA et al, 2012). Clinical manifestations have been absent or mild among New World monkeys infected with Platynosomum, although some deaths have also be attributed to the parasite (MELO, 2004;SOUSA et al, 2008;SILVA et al, 2012).…”
mentioning
confidence: 99%
“…(KINGSTON & COSGROVE, 1967;COSGROVE et al, 1968;SHANTA, 1970;PORTER, 1972;TANTALEAN et al, 1990;WARREN et al, 1998;MELO, 2004;KAWHAGE et al, 2005;SOUSA et al, 2008;SILVA et al, 2012). Clinical manifestations have been absent or mild among New World monkeys infected with Platynosomum, although some deaths have also be attributed to the parasite (MELO, 2004;SOUSA et al, 2008;SILVA et al, 2012). The prognosis of the disease depends on the severity of chronic fibrosing hepatopathy, which is likely to be correlated with the parasite burden and the individual infected host response (SOUSA et al, 2008).…”
mentioning
confidence: 99%